Differences in the situational parameters of tennis matches between winners and losers in the women´s main draw competition at ROLAND GARROS 2022 - Bilic, Z. (Studia Sportiva, 2022)
Several studies investigated the situational efficiency parameters at tennis matches in the men's and women's competition at previous Rolland Garros tournaments. The aim of this study was to determine if there are differences in the situational efficiency parameters between winners and losers in the women's main draw competition at Roland Garros 2022. This study included 125 main draw matches. Differences in performance were analysed across 7 situational efficiency variables: aces, double faults, 1st serve average speed, 2nd serve average speed, winners, unforced errors and forced errors. The results showed significant differences between winners and losers with the following parameters on the winners` side: number of aces per match (2.40/1.63; p = 0.03), winners (24.83/19.37; p = 0.00), unforced errors (23.80/29.13; p = 0.00) and forced errors (19.71/23.64; p = 0.00). The results demonstrated that there were no significant differences in double faults, 1st serve average speed and 2nd serve average speed. More aces of winners can indicate better service accuracy and variability, as there is no significant difference in service speed. Also, a more successful start of a point can positively affect the early dominance in the point rally and easier achieving of winners. In addition to all the above, it is notable that more successful tennis players, as well as having more winners, record less unforced and forced errors. The information obtained should be used by tennis coaches in planning trainings and preparing matches in order for their tennis players to achieve maximum results.